Assessing Consensus: The Promise and Performance of Negotiated Rulemaking - Cary Coglianese (My University, 2016)
This article presents an empirical assessment of the impact of negotiated rulemaking on two of its principal goals: reducing overall rulemaking time and decreasing the number of judicial challenges to agency rules. Unlike other research, this analysis considers the use of regulatory negotiation by all federal agencies over the past thirteen years. Like others, it gives special attention to rulemaking at the EPA because it has pursued by far the most negotiated rulemakings and it has been the focus of many of the claims about the purported success of the negotiated process.